Rubicon-deficiency sensitizes mice to mixed lineage kinase domain-like (MLKL)-mediated kidney ischemia-reperfusion injury - Tonnus, Wulf (2022)
The cytosolic protein rubicon (RUBCN) has been implicated in the removal of necrotic debris and autoimmunity. However, the role of RUBCN in models of acute kidney injury (AKI), a condition that typically involves necrotic kidney tubules, was not investigated. Here, we demonstrate that RUBCN-deficient mice are hypersensitive to renal damage induced by ischemia-reperfusion injury (IRI) and cisplatin-induced AKI. Combined deficiency of RUBCN and mixed lineage kinase domain-like (MLKL) partially reversed the sensitivity in the IRI model suggesting that the absence of RUBCN sensitizes to necroptosis in that model. Necroptosis is known to contribute to TNFα-induced severe inflammatory response syndrome (SIRS), but we detected no statistically significant difference in overall survival following injection of TNFα in RUBCN-deficient mice. We additionally generated RUBCN-deficient mice which lack gasdermin D (GSDMD), the terminal mediator of pyroptosis, but no reversal of the AKI phenotype was observed. Finally, and in contrast to the previous understanding of the role of RUBCN, we did not find a significant autoimmune phenotype in RUBCN-deficient mice, but detected chronic kidney injury (CKD) in aged RUBCN-deficient mice of both sexes. In summary, our data indicate that RUBCN-deficient mice are hypersensitive to kidney injury.